PENGEMBANGAN WEBSITE DORATOON SEBAGAI MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI PADA MATERI ORGAN PERNAPASAN - Widiya Pangesti, Heni; Saniyatus Salamah, Bintun; Oktania Aslorida, Bella; Nafhatin, Izza (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This study aims to develop the Doratoon website as a technology-based learning medium for respiratory system materials. In this digital era, the use of technology in education has become increasingly important to enhance the effectiveness and attractiveness of learning. The Doratoon website provides tools for creating educational animation videos that can be uploaded to platforms such as YouTube. The research method used is research and development (R&D) with the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The results of the study indicate that the use of the Doratoon website as a learning medium is effective in improving students' understanding of the respiratory system and makes learning more interactive and engaging.